Investigating the relationships between wheat-specific rainfall characteristics, large-scale modes of climate variability and wheat yields in the Swartland region, South Africa - Kloppers,Pierre-Louis (Department of Environmental and Geographical Science, 2015)
Includes bibliographical references.